Defining Unstageable Pressure Ulcers as Full-Thickness Wounds: Are These Wounds Being Misclassified?. Issue 6 (November 2015) - Zaratkiewicz, Sunniva; Whitney, JoAnne D.; Baker, Margaret W.; Lowe, Jeanne R.
Abstract : PURPOSE: The purpose of this study was to describe the evolution of unstageable pressure ulcers (PUs) over time to determine if their healing trajectory is consistent with full- or partial-thickness wounds. DESIGN: Retrospective review of electronic medical record and a clinical PU database. SUBJECTS AND SETTINGS: Patients with hospital-acquired, unstageable PUs were evaluated. Subjects were cared for at a level 1 trauma/burn center and safety net hospital in the Pacific Northwest between November 2007 and March 2011. METHODS: Electronic medical records and a clinical PU database for 194 unstageable PUs were examined. The PU database is managed by certified wound care nurses; it includes data on all verified hospital-acquired PUs since 2007. The unit of analysis for this study was the individual PU site. RESULTS: Of the initial 194 unstageable PUs identified, 120 were excluded due to lack of data needed to address research questions. Out of the 74 unstageable PUs that remained in the study, approximately one-third (33.8%) were found to follow a healing trajectory consistent with partial-thickness wounds. CONCLUSION: Findings indicate that while approximately two-thirds of unstageable PUs demonstrate healing trajectories consistent with full-thickness wounds, slightly more than a third follow a trajectory consistent with partial-thickness wounds. Additional research is needed to clarify the healing trajectories of unstageable PUs and to determine whether the current definition for unstageable PUs is adequate.